Cone cavernoma with a twice secondary intramedullary hemorrhage - Patricia Alejandra Garrido Ruiz; Marta Román Garrido (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2023)
Possible complications that may occur and how to solve them before surgery are essential. This case is of special interest for being a low-incidence pathology in a rare location. The case is of high interest because of the importance of evacuating the hemorrhage to prevent sequels and the complexity of its management and highlights the importance of considering the diagnosis of this event.